Differentially localized rice ethylene receptors OsERS1 and OsETR2 and their potential role during submergence. (3rd August 2017) - Yu, Manda; Yau, Chi Ping; Yip, Wing Kin
ABSTRACT: Ethylene is gaseous plant hormone that controls a variety of physiologic activities. OsERS1 and OsETR2 are major ethylene receptors in rice that have been reported to have different regulatory functions. The GFP fused N-terminus of OsERS1 and OsETR2 showed differentially localization patterns when transiently expressed in onion epidermal cells. Base on these results, we suggested that OsERS1 could be localized to plasma membranes, whereas OsETR2 could be localized to the endoplasmic reticulum. Furthermore, instead of the constitutive expression profile of OsERS1, OsETR2 is differentially expressed in seedlings of light/dark-grown conditions, submergence or exogenous ethylene treatments. Our results and others support the notion that OsERS1 and OsETR2 could have different roles during rice plant submergence.